PENGARUH SOSIAL EKONOMI ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK PEMULUNG DI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH TALANG GULO KOTA JAMBI - Usi Doris Panjaitan, Diliza Afrila (Universitas Batanghari Jambi, 2020)
Abstract This study aims to determine (1) the socioeconomic picture of parents in TPA Talang Gulo Jambi City, (2) The description of the level of education of scavengers in Talang Gulo TPA Jambi City, (3) The socioeconomic influence of parents on the level of scavenger children's education in TPA Talang Gulo Jambi City. The results showed that (1) Parental socioeconomic in the Talang Gulo Garbage Landfill (Jambi TPA) is quite good. This is indicated by the parent's socioeconomic average of 3.29 with a Respondent Achievement Rate (TCR) of 65.72. (2) The education level of scavenger children in the Talang Gulo Garbage Landfill (TPA) in the City of Jambi is quite good. This is indicated by the average level of education of scavenger children belonging to the Secondary Education Level (SMA/SMK) of 59 children or 54.13% of 109 respondents. (3) The socioeconomic parents have a significant effect on the level of education of scavengers in the Talang Gulo Garbage Landfill in Jambi City. This is indicated by tcount > ttable or 2.423 > 0.017. The contribution of parents' socioeconomic variables to children's education level is 5.2%, and the remaining 94.8% is influenced by other factors not examined. Keywords: Socio-Economic Parents, Children's Education